Keputusan Berkunjung Pada Destinasi Wisata : Peran Aksesibilitas, Digital Marketing dan Fasilitas - dikdik harjadi (Jurnal Manajemen dan Bisnis Kreatif)
The purpose of this study was to determine the effect of accessibility, digital marketing, and facilities on the decisions to visit partially and simultaneously. The type of research used is quantitative. The method used in this research was descriptive and verification method. The sample or respondents in this study were adjusted to be 100 people (tourists). This makes it easier to process data and for better test results. In collecting data using documentation and questionnaire techniques. The questionnaire scale used was an interval scale of 1 to 10. The calculation to test the proposed hypothesis uses multiple linear regression analysis with the help of the SPSS for windows version 25 application. The results show: (1) Accessibility, digital marketing, and facilities affect the decisions to visit at the Balong Dalem tourist attraction. This means that every change in the decisions to visit is influenced by factors of accessibility, digital marketing, and facilities, (2) Accessibility has a positive and significant effect on the decisions to visit the Balong Dalem tourist attraction. This means that proper accessibility can increase the decisions to visit, (3) Digital marketing has a positive and significant effect on the decisions to visit the Balong Dalem tourist attraction. This means that effective digital marketing can improve visiting decisions, and (4) Facilities have a positive and significant effect on decisions to visit Balong Dalem tourism objects. This means that complete facilities can improve visiting decisions